Determinants of individuals' participation in integrated chronic disease screening in Singapore. Issue 12 (10th June 2016) - Venkataraman, Kavita; Wee, Hwee Lin; Ng, Sheryl Hui Xian; Rebello, Salome; Tai, E Shyong; Lee, Jeannette; Tan, Chuen Seng
Abstract : Background: A large pool of patients with chronic diseases remains undiagnosed globally and in Singapore. We explored factors associated with participation in a health screening exercise, using revealed preference, that is, actual attendance, to understand why people remain undiagnosed with chronic diseases. Methods: A cross-sectional, community-based sample of Singapore residents was invited to participate in home interviews, and subsequently to attend centre-based health screening, between 2004 and 2007. Determinants of health screening participation were identified using logistic regression models based on Andersen's Behavioral Model. Results: Of the 6366 participants who completed health interview, 4092 attended the health screening, while 2274 did not. Older age, Chinese or Indian ethnicity, higher education levels, greater intake of monounsaturated fat, greater transport and leisure-time physical activity were the key predisposing factors associated with greater health screening participation. Greater family cohesion was the key associated enabling factor, while previous diagnosis of dyslipidaemia or musculoskeletal conditions, absence of previously diagnosed diabetes or hypertension and lower perceived physical health were the associated need factors. Conclusions: Our study suggests that ethnicity, education, family cohesion, healthy behaviour patterns and perceived physical health status were key determinants of health screening participation. Enhancing the cultural competence of preventive health services may help increase participation of these groups in screening efforts and reduce the proportions of undiagnosed chronic disease in the community.